2021
DOI: 10.1136/neurintsurg-2021-017441
|View full text |Cite
|
Sign up to set email alerts
|

Early recanalization in large-vessel occlusion stroke patients transferred for endovascular treatment

Abstract: BackgroundWe performed an exploratory analysis to identify patient and thrombus characteristics associated with early recanalization in large-vessel occlusion (LVO) stroke patients transferred for endovascular treatment (EVT) from a primary (PSC) to a comprehensive stroke center (CSC).MethodsWe included patients with an LVO stroke of the anterior circulation who were transferred to our hospital for EVT and underwent repeated imaging between January 2016 and June 2019. We compared patient characteristics, workf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Achieving early reperfusion in an acute ischemic stroke strongly influences clinical outcomes 1–4 . In large vessel occlusion (LVO) patients treated with intravenous alteplase, the reported rates of thrombolytic agent‐induced reperfusion prior to endovascular therapy ranges from 10 to 30% 5–8 .…”
Section: Introductionmentioning
confidence: 99%
“…Achieving early reperfusion in an acute ischemic stroke strongly influences clinical outcomes 1–4 . In large vessel occlusion (LVO) patients treated with intravenous alteplase, the reported rates of thrombolytic agent‐induced reperfusion prior to endovascular therapy ranges from 10 to 30% 5–8 .…”
Section: Introductionmentioning
confidence: 99%
“…Lower thrombus extent was found to be critical for the effectiveness of IV-tPA [57] and associated with early recanalization following IV-tPA treatment [81], and thrombus length was found a powerful independent predictor of no-early recanalization following IV-tPA treatment in minor strokes [82]. Short SVS was found to be a predictor of excellent outcome at 3 months in patients with stroke with LVO treated with IV-tPA alone [71].…”
Section: Clot Extent Location and Shapementioning
confidence: 96%
“…It was found that the occlusion location is a predictor for RBC content [38], and it is associated with postprocedural hemorrhage [54]. Early recanalization following IV-tPA treatment was associated with more distal occlusion [81]. As compared with patients with severe stroke, patients with mild stroke had more distal occlusions [62].…”
Section: Clot Extent Location and Shapementioning
confidence: 99%
“…Indeed, IVT may facilitate cerebral reperfusion and arterial recanalization. It has been well identified that M2 occlusions have higher chances of early recanalization after IVT than intracranial internal carotid artery or M1 occlusions 14 15. However, MT in M2 occlusion can also be more challenging, involving more distal arteries potentially increasing operative risk 16–18.…”
Section: Introductionmentioning
confidence: 99%